2019
DOI: 10.2478/rjdnmd-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients and Oral Health an Opportunity to Prevent Oral Diseases

Abstract: Nutrition plays an important role in oral health as it affects the growth of craniofacial, dental and periodontal structures. When adequate food is not unavailable, oral health may be impaired, and even overexposure to the diet may also inversely affect. Therefore, there is interdependency between nutrition and oral health. The importance of Micronutrients in normal function is becoming increasingly apparent and insufficient micronutrient intake has both short term and long-term consequences. Micronutrient ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The observation showed that thecaries-free group had a higher level of copper 35 . It has been shown to inhibit S-H containing enzymes on rodents, which may impede acid production in dental plaque and caries 36 . Deficiency of zinc and copper increases the risk of infectious diseases 37 .…”
Section: Zinc and Coppermentioning
confidence: 99%
See 1 more Smart Citation
“…The observation showed that thecaries-free group had a higher level of copper 35 . It has been shown to inhibit S-H containing enzymes on rodents, which may impede acid production in dental plaque and caries 36 . Deficiency of zinc and copper increases the risk of infectious diseases 37 .…”
Section: Zinc and Coppermentioning
confidence: 99%
“…Istovremeno, treba da budemo svesni toksičnih efekata fluoride, koji mogu dovesti do pojave fleka na zubima od blagih, bele boje (Slika 3), do ekstremno izraženih, braonkaste prebojenosti i doprineti formiranju rupica u gleđi 36 . Kao što je pomenuto , nedostatak fluorida može dovesti do povećanja zubnog karijesa, ali ne utiče na sluzokožu.…”
Section: Fluorineunclassified